2009
DOI: 10.1590/s0103-97332009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oil shale residue and rejects from irati formation by electron paramagnetic resonance

Abstract: In this study, sedimentary organic matter of oil shale rejects, calschist, shale fine and the so called retorted shale from Irati formation was characterized. EPR was used to analyse the samples regarding loss of signal in g = 2.003 associated to the organic free radical with the calcined samples and washing with hydrogen peroxide. The radical signal was detected in all samples, however, for the calschist and shale fine samples another signal was identified at g = 2.000 which disappeared when the sample was he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Moreover, the hyperfine structure of the EPR spectrum (when it is well resolved) provides more important information about the radical than the g-value, because most radicals detected are carbon or nitrogen centered radicals and the spectra positions are almost in the same magnetic field range [1]. The EPR technique has been widely used for long time in the identification of irradiation damage centers in many substances including drugs, amino acid and iminodiacetic acid derivatives [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. L-glutamine and iminodiacetic acid powders were gamma-irradiated and studied by EPR at room temperature [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hyperfine structure of the EPR spectrum (when it is well resolved) provides more important information about the radical than the g-value, because most radicals detected are carbon or nitrogen centered radicals and the spectra positions are almost in the same magnetic field range [1]. The EPR technique has been widely used for long time in the identification of irradiation damage centers in many substances including drugs, amino acid and iminodiacetic acid derivatives [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. L-glutamine and iminodiacetic acid powders were gamma-irradiated and studied by EPR at room temperature [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of a well-determined spectrum of Mn 2+ in crude oil. A not so clear spectrum due to Mn 2+ impurities was reported for a Venezuelan oil, and the presence of Mn 2+ in oil shale and sand bitumen is well-known.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast with the isotropic X-band spectra, W-band spectra of diesel were found to show poorer signal-to-noise ratios and anisotropy in the A-and g-parameters 131 . EPR has also been used to characterise oil shale residue and rejects, calschist, shale file and retorted shale from the Irati formation in Brazil 132 . A study was reported of various fuel-samples made using ESR.…”
Section: Fuel-related Applicationsmentioning
confidence: 99%